Facile Synthesis of Novel Glycosyl Oxindoles through 1,3-Dipolar Cycloaddition - Sirisha, N.; Raghunathan, R. (Synlett, 2013)
Synthesis of a series of glycosyl spirooxindoles has been accomplished through an intermolecular 1,3-dipolar cycloaddition reaction of an azomethine ylide generated from glucose with the dipolarophile 4-(E)-3-phenacylidene oxindole.
Keywords: 1,3-dipolar cycloaddition; azomethine ylide; spirooxindoles; pyrrolidines; glycosyl heterocycles